A3.12 Intrarenal Foxp3+ Regulatory T Cells Expansion and Decreased Number of Infiltrating CD4+ T Cells in Murine Lupus by IL-2 Therapy. (25th February 2013) - Rose, A; Humrich, JY; Riemekasten, G
Abstract : Background and Objectives: Systemic lupus erythematosus (SLE) is an autoimmune disease characterised by an acquired IL-2 deficiency, which leads to a homeostatic imbalance between regulatory T cells (Treg) and effector T cells (Tcon). Humrich et al, (2010) demonstrated that the IL-2 deficiency in diseased (NZB × NZW) F1 mice can be rebalanced in lymphoid organs using a treatment with recombinant IL-2 (IL-2) by promoting the homeostatic proliferation of regulatory T cells. The aim of this study was to investigate the impact of IL-2 therapy on intrarenal Foxp3+ Treg and kidney infiltrating CD4+ cells in (NZB × NZW) F1 mouse model of lupus nephritis. Materials and Methods: (NZB × NZW) F1 mice with active nephritis were treated with recombinant IL-2 either over a short period or for a total of 30 days. Absolute numbers, phenotype and proliferation of kidney infiltrating CD4+ T cells were determined by flow cytometry. Results: (NZB × NZW) F1 mice treated over a short term with IL-2 showed an enhanced proliferation of Foxp3+ Treg and increased numbers and frequency of CD4+Foxp3+ Treg compared to un-treated treated control mice. On the other hand, long term IL-2 treatment did not result in a persistent expansion of the intrarenal Foxp3+ Treg population. Nevertheless, total numbers of kidney infiltrating CD4+ T cells were diminished and the CD4+ T con showed reduced signs of cellular activation. Conclusions: Our data indicates that short term IL-2 treatment is able to expand the size of the intrarenal Treg pool. In contrast, long term IL-2 treatment decreases the numbers of kidney infiltrating CD4+ T cells. These results may in part explain the delay of disease progression induced by treatment with IL-2 and underline the important role of intrarenal Treg for the suppression of kidney disease in lupus mice. These results also provide additional rationales for an IL-2 based immunotherapy of human disease.